Representing Sexual Violence in Indonesian Cinema: A Semiotic Analysis of Woman from the Rote Island - Tania Salsabela; Hetty Catur Ellyawati (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to critically examine how the representation of sexual violence against women is constructed in the film Woman from the Rote Island through the analysis of denotative, connotative, and mythological meanings. The main focus is to reveal the social messages, ideologies, and positions of women in patriarchal power relations represented by cinema. Thus, the research is directed to assess the role of film as a medium of social criticism and shaping public awareness. Theoretical framework: This study uses Roland Barthes' semiotic theory, which emphasizes the meaning of denotation, connotation, and myth. This framework is used to read signs and symbols in movies. With this approach, patriarchal ideology can be critically analyzed. Literature review: A literature review discusses research on women's representation and sexual violence in film media. Previous studies have shown that movies can reinforce or challenge patriarchal values. This literature became the basis for placing film as part of social discourse. Methods:  The method used is qualitative descriptive with semiotic analysis. Data is obtained from scenes, dialogue, and visual symbols in the film. The analysis was carried out by relating the findings to three levels of Barthes' meaning. Results: The results of the study show that films represent women as victims of physical, psychological, and social violence, as well as subjects who have courage and moral strength. On a connotative and mythological level, the film deconstructs the myth of women's honor shaped by patriarchy. The film's narrative emphasizes that sexual violence is a violation of humanity, not a disgrace to the victim. Implications: This study shows that film can be a medium of education and social criticism. These findings encourage the use of cinema to increase empathy and awareness about women's rights. Another implication is the strengthening of the discourse on gender equality in the public space. Novelty: The novelty of this research lies in the use of Barthes' semiotics to read the issue of sexual violence in Indonesian films. The study emphasizes women not only as victims, but also as agents of symbolic resistance. Thus, film is understood as a tool for cultural change.